2004
DOI: 10.1111/j.1346-8138.2004.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cells in the Vellus Hair Follicles of Human Facial Skin: A Study Using Confocal Laser Microscopy

Abstract: Many cases of Merkel cell carcinoma have recently been reported, and most of them have been localized on the facial skin. In this study, we investigated Merkel cells in the vellus hair follicles of facial region to characterize these cells in human subjects. Skin specimens doubly stained with cytokeratin (CK) 20 and either protein gene product (PGP) 9.5 or vasoreactive intestinal polypeptide (VIP) were examined by confocal laser microscopy. Many of the Merkel cells in the vellus hair follicles of the facial sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The proliferation of these cells seems to involve a differentiation from their precursor that may reside in the dermis. In a recent study it was postulated that non-innervate Merkel cells in the skin could be undifferentiated or immature elements (Uchigasaki et al, 2004). Moreover, Narisawa et al (1992) shown that in the human embryos Merkel cells express nerve growth factor (NGF) receptor just before epidermal innervations suggesting a role in this physiologic process.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of these cells seems to involve a differentiation from their precursor that may reside in the dermis. In a recent study it was postulated that non-innervate Merkel cells in the skin could be undifferentiated or immature elements (Uchigasaki et al, 2004). Moreover, Narisawa et al (1992) shown that in the human embryos Merkel cells express nerve growth factor (NGF) receptor just before epidermal innervations suggesting a role in this physiologic process.…”
Section: Discussionmentioning
confidence: 99%
“…dendritic or round cells. In addition, MCs can be found with and without association to nerve Wbers (Fantini and Johansson 1995;Narisawa and Kohda 1995;Tachibana et al 2001;Uchigasaki et al 2004). The various putative functions ascribed to MCs might also be allocated to distinct populations.…”
Section: Introductionmentioning
confidence: 97%
“…The localization of the cilia-associated Merkel cells is similar to that described for the hair of the head, 9 however their number did not reach those described in the literature. 10 Since Merkel cells at this location are not constantly innervated, 11 their mechanosensitive function is questionable.…”
Section: Discussionmentioning
confidence: 99%